Hubungan Pengetahuan dengan Sikap Wanita Usia Subur (WUS) terhadap Kesehatan Reproduksi Wanita Di Wilayah Kerja Puskesmas Guntung Payung Kota Banjarbaru Tahun - Siti Hardiyanti (Jurnal Kesehatan Indonesia, 2018)
The reproductive health is defined as a condition that ensures that the reproductive function, especially the reproductive proses can take place in a statw of physical, mental and social prosperity and not just free from disease or impaired reproductive function. The purpose of this research is to know the correlation of knowledge with the attitude of women fertile age about women reproductive health in working area of Puskesmas Guntung Payung Kota Banjarbaru 2017. This research was concluded at Puskesmas Guntung Payung Kota Banjarbaru by using analytical survey method which started from may – June 2017. The population of this research were women fertile age in working area of Puskesmas Guntung Payung Banjanrbaru which number of 150 people and took 600 respondents as the samples by using purposive sampling technique. The result of this research indicated that women of reproductive age who were less knowledge about women reproductive health were 29 (48.3%), 27 (45%) fair and 4 (6,7%) knowledgeable. The spearman test result obtained p value 0,031 ( = 0,05) which mean there was correlation of knowledge with was correlation of knowledge with the attitude of women fertile age to reproductive health of women. Key word : Knowledge, attitude, women fertile age